And then there were many: insights from the tangled taxonomy of the Antarctic brittle star Ophioplinthus gelida (Echinodermata: Ophiuroidea) - Chester J. Sands; Timothy D. O’Hara; Alice Guzzi; William P. Goodall-Copestake; Peter Convey; Bhavani E. Narayanaswamy; Rafael Martín-Ledo; Sabine Stöhr (Frontiers in Marine Science, 2025)
To effectively manage biological assemblages, a sound knowledge of the biodiversity is essential. The Southern Ocean shelf benthic assemblages are typically comprised of species, the names of which are shared across the huge expanse of the region, indicating large population sizes and good connectivity, inferring resilience. This is despite two decades of studies identifying cryptic or unrecognised species in many benthic groups. In this study we examine the common and widespread species Ophioplinthus gelida (Koehler, 1900) and Ophioplinthus martensi (Studer, 1885), both regarded as occurring throughout the Southern Ocean on continental and island shelves. The two species show subtle differences in morphology, despite O. gelida having very plastic character states. Genetic analysis using mitochondrial sequences shows that the two species are part of a radiating clade with ten distinct elements, six of which group as O. gelida and four as O. martensi . Further investigation showed that one of these elements can be attributed to Ophioplinthus carinata (Studer, 1876), not previously identified on the Antarctic shelf, but shown here to be a dominant fraction of the O. “gelida” in our collections. Furthermore, O. “martensi” from its type locality of South Georgia is genetically similar to Ophioplinthus intorta (Lyman, 1878), from Marion Island, but distinct from those collected from the Antarctic shelf, which may then be considered Ophioplinthus inermis (Bell, 1902). A fifth clade of O. martensi collected from waters deeper than 2000 m was not part of this radiation but grouped together with more distantly related Ophioplinthus species. In general, the genus displays a wide range of morphological character states, varying greatly within O. gelida elements, and often shared between species. Several taxa outside of the O. gelida complex may also include unrecognised cryptic species, making reliable field identifications challenging, and greatly increasing the recognised species diversity and regional endemism.

Corrigendum to “A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa” [Biol. Conserv. 284 (2023) 110163] - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

Plants with arbuscular mycorrhizal fungi efficiently acquire Nitrogen from substrate additions by shaping the decomposer community composition and their net plant carbon demand - Somak Chowdhury; Markus Lange; Ashish A. Malik; Timothy Goodall; Jianbei Huang; Robert I. Griffiths; Gerd Gleixner (Plant and Soil, 2022)
Aims We investigated the role of plants and their plant-derived carbon in shaping the microbial community that decomposes substrates and traced the return of nutrients from decomposition back to plant shoots in order to understand the importance of plants for ecosystem element cycling. Methods We performed a greenhouse experiment having plant communities with and without arbuscular mycorrhizal fungi (AMF) and ingrowth cores that held different 15 N labeled substrates. We determined the microbial community structure using molecular sequencing and the net assimilation of plant carbon into soil microorganisms using a 13 CO 2 pulse and 13 C measurements of microbial biomarkers. We determined the return of nitrogen back to the shoots using the 15 N signal, which was provided from the decomposition of the substrate added to the ingrowth cores. Results We observed that the microbial community composition in the ingrowth cores and their net 13 C assimilation depended on the presence of AMF and the added substrate. Both plant communities had similar 15 N uptake into their shoots, but the net N uptake cost was significantly lower in presence of AMF. In the presence of AMF also lower net N uptake cost was observed for the decomposition of plant-derived and microorganism-derived substrates compared to inorganic nitrogen suggesting that AMF actively controls the decomposer comunity and their carbon demand. Conclusion Our results identify for the first time a functional overlap of soil microorganisms as identical substrate is decomposed by different microorganisms suggesting functional redundancy of microbial communities. In consequence a better understanding of ecosystem element cycling can only be achieved when the whole plant-microorganism-organic matter-soil continuum is investigated.